The First 100 Days of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Control in Vietnam. (1st August 2020) - Thai, Pham Quang; Rabaa, Maia A; Luong, Duong Huy; Tan, Dang Quang; Quang, Tran Dai; Quach, Ha-Linh; Hoang Thi, Ngoc-Anh; Dinh, Phung Cong; Nghia, Ngu Duy; Tu, Tran Anh; Quang, La Ngoc; Phuc, Tran My; et al.
Abstract: Background: One hundred days after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Vietnam on 23 January, 270 cases were confirmed, with no deaths. We describe the control measures used by the government and their relationship with imported and domestically acquired case numbers, with the aim of identifying the measures associated with successful SARS-CoV-2 control. Methods: Clinical and demographic data on the first 270 SARS-CoV-2 infected cases and the timing and nature of government control measures, including numbers of tests and quarantined individuals, were analyzed. Apple and Google mobility data provided proxies for population movement. Serial intervals were calculated from 33 infector-infectee pairs and used to estimate the proportion of presymptomatic transmission events and time-varying reproduction numbers. Results: A national lockdown was implemented between 1 and 22 April. Around 200 000 people were quarantined and 266 122 reverse transcription polymerase chain reaction (RT-PCR) tests conducted. Population mobility decreased progressively before lockdown. In total, 60% (163/270) of cases were imported; 43% (89/208) of resolved infections remained asymptomatic for the duration of infection. The serial interval was 3.24 days, and 27.5% (95% confidence interval [CI], 15.7%-40.0%) of transmissions occurred presymptomatically. Limited transmission amounted to a maximum reproduction number of 1.15 (95% CI, .·37–2.·36). No community transmission has been detected since 15 April. Conclusions: Vietnam has controlled SARS-CoV-2 spread through the early introduction of mass communication, meticulous contact tracing with strict quarantine, and international travel restrictions. The value of these interventions is supported by the high proportion of asymptomatic and imported cases, and evidence for substantial presymptomatic transmission. Abstract : Vietnam has controlled severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread through early mass communication, contact tracing, quarantine, and travel restrictions. In total, 60% of the 270 cases were imported, 43% were asymptomatic and 27% of transmissions occured before symptoms.